6 Shipwreck archaeology in the past 10 years - Briggs, Lisa; Campbell, Peter B. (Cambridge University Press (CUP), 2023)
This paper reviews the trends, topics, and research directions in shipwreck archaeology over the past decade. As archaeology increasingly embraces advances in technological methods that can aid our research, the so-called ‘digital turn’, it behoves maritime archaeologists, and archaeologists more broadly, to consider how collaborative utilization of specialized fields including biomolecular archaeology, geophysics, and contemporary philosophy have spurred on a rapid modernization of our field in recent times. Archaeological research, both terrestrial and underwater, has long been a collaborative discipline. However, we argue here that difficulties in working underwater have encouraged maritime and underwater archaeologists to embrace technological developments at a rapid pace. An explicit theoretical framework and the incorporation of contemporary philosophy in the field of underwater archaeology was, until recently, largely lacking in the discipline’s discourse. The incorporation and advancement of adjacent disciplines within the field of underwater archaeology mark the most relevant changes within the shifting tides of shipwreck research.